1995
DOI: 10.1037/0022-3514.69.4.778
|View full text |Cite
|
Sign up to set email alerts
|

A prospective test of an integrative interpersonal theory of depression: A naturalistic study of college roommates.

Abstract: This study tested an integrated interpersonal theory of depression, which combines J. C. Coyne's (1976b) interpersonal theory of depression with work on the interplay between self-enhancement and self-consistency theory. Students' (targets') and their same-gender roommates' appraisals of each other, depression and anxiety levels, reassurance seeking, and negative feedback seeking were assessed at Time 1 (T1), and again at Time 2 (T2), 3 weeks later. Consistent with the theoretical integration (a) Depressed tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
213
4
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(234 citation statements)
references
References 58 publications
(158 reference statements)
14
213
4
3
Order By: Relevance
“…In her recent follow-up study, Rose and colleagues (2007) 1995;Joiner & Metalsky, 1995;La Greca & Lopez, 1998; Starr & Davila, in press), and the same is likely to be true for co-rumination. Social anxiety is defined by social avoidance (American Psychiatric Association, 1994).…”
Section: Distinguishing Types Of Internalizing Symptomsmentioning
confidence: 94%
See 1 more Smart Citation
“…In her recent follow-up study, Rose and colleagues (2007) 1995;Joiner & Metalsky, 1995;La Greca & Lopez, 1998; Starr & Davila, in press), and the same is likely to be true for co-rumination. Social anxiety is defined by social avoidance (American Psychiatric Association, 1994).…”
Section: Distinguishing Types Of Internalizing Symptomsmentioning
confidence: 94%
“…However, some evidence suggests that the factor structure of the symptoms of depression and anxiety shifts with age (Lahey et al, 2004). For example, Cole, Truglio, and Peeke (1997) found support for a one factor model in childhood, but showed that separate factors emerged by early adolescence, suggesting they are best examined separately.In her recent follow-up study, Rose and colleagues (2007) 1995;Joiner & Metalsky, 1995;La Greca & Lopez, 1998; Starr & Davila, in press), and the same is likely to be true for co-rumination. Social anxiety is defined by social avoidance (American Psychiatric Association, 1994).…”
mentioning
confidence: 94%
“…Ratings are summed across the 4 items to yield scores ranging from 4 to 28, with higher scores indicating higher levels of reassurance seeking. The scale has been shown to have good criterion and construct validity, including discriminant validity from dependency and negative affectivity, and predictive validity of actual reassurance seeking behaviors (Joiner, 1994;Joiner et al, 1992Joiner et al, , 1993Joiner & Metalsky, 1995;Potthoff et al, 1995). In studies by Joiner and colleagues, internal consistency has ranged from .85 to .95.…”
Section: Experiences In Close Relationships-revised (Ecr-r)mentioning
confidence: 99%
“…Responses are recorded on a 1 ("definitely yes") to 6 ("definitely no") scale. The WILL shows adequate internal consistency (α = .85; Joiner & Metalsky, 1995).…”
Section: Methodsmentioning
confidence: 99%